A hybrid system for voltage stability and placement optimization of STATCOM in distribution systems - Ms. Shweta Chourasia, Dr I.D Soubache,Dr.P.Gomathi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A methodology is provided in this paper for determining the optimal assignment (i.e., sizing and position) of Distributed Generators (DGs) and static compensators (STATCOM) in a radial distribution system (RDS). The voltage stability index (VSI) is used to locate the best STATCOM position, and the fast voltage stability index (FVSI), and phase voltage stability index (PVSI) are used to locate the best-distributed energy location. The suggested work is presented as a non-linear optimal solution with a hybrid power stability optimization (HPSO), which is solved utilising a meta-heuristic/evolutionary-based approach in this paper. The Bat method is used to determine the ideal dimensions of STATCOM in RDSs. Two basic IEEE 34 and 85 bus RDSs are investigated in this study to assess the correctness, feasibility, and applicability of the suggested optimal allocating method. In the RDSs, the experiments demonstrate a reduction in energy losses and an increase in bus voltages.